Validitas Multimedia Interaktif Berbasis Android Terintegrasi Ispring Pada Materi Protista Kelas XSMA - Fira Farizka; Lufri Lufri; Syamsurizal Syamsurizal; Relsas Yogica (JURNAL PENDIDIKAN ROKANIA, 2022)
Technology and information in the era of the Industrial revolution 4.0 greatly affects all aspects of life in the field of education. The use of technology in the learning process makes students more active in learning. Likewise with the 2013 curriculum which requires students to study and seek information about independent learning materials. Therefore, learning media is needed that can increase interest and motivation to learn. One of the media that can be used is interactive multimedia based on Android. This research was conducted to test the validity of the integrated Android-based interactive multimedia on the protist material for class X SMA to be developed. This multimedia was developed using three stages of a 4-D model, namely define, design, and develop. The object of this research is interactive multimedia based on Android integrated in protist material for class X SMA. The multimedia was validated by 2 biology lecturers, FMIPA UNP and 1 biology teacher at SMAN 12 Padang by providing a validation questionnaire. The results of this study are interactive multimedia based on Android integrated in the protist material of class X SMA has an average value of 83,26 and is included in the valid category.